PENYEBARAN GUMPALAN DALAM PEMBULUH DARAH (DISSEMINATED INTRAVASCULAR COAGULATION) AKIBAT RACUN GIGITAN ULAR - Prihatini .; Trisnaningsih .; muchdor .; U N Rachman (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Cases of snake bites were seldom happened in town. From the 2500–3000 world-wide distributed species of snakes, 500 are venomous. The snake produce some toxic substance which is dangerous in men , and could cause morbidity or mortality. It’s caused byophitoxaemia, which influence the permeability of capilers with consequence bleeding. There patients must be examined physically, localas well systemic. The laboratoric examinations were based on clinical symptoms, by determination of the snake venom causal and thesequalae in the human body, including coagulopathy, anemia as well as renal failure, etc. The snake venom may cause necrotic tissue offoot and anemia by trombocytopenia.The condition of this victim patient was severre due to his diabetic syndrome. This article presenteda study of snake bite incident on an old man with DIC laboratoric results, following anemia and renal failure which caused his death.